PENINGKATAN EKONOMI MASYARAKAT DI DAERAH WISATA BATU BELIMBING KELURAHAN NYARUMKOP SINGKAWANG TIMUR KOTA SINGKAWANG - Mahendra Jaya; Ismail Umar; Edy Sutrisno; Novi Desanti; Anggita Anggita; Laila Nurfitrah Lubis; Debbie Yuari Siallagan (Nindikayla Institute, 2023)
Not a few people are affected by the Covid-19 pandemic, one of which is the impact felt on the economic aspect. The risk of lack of income and loss of livelihood has been felt by residents of the Batu Belimbing Tourism Area, Nyarumkop Village, Singkawang City. The purpose of community service is carried out in order to awaken the entrepreneurial spirit by providing counseling related to economic improvement. One of the counselling activities is by providing skills training in batik. The result of this activity is that community members have and develop batik skills that can be used to build new businesses to increase people's income